Nitric oxide mediates N-methyl-d-aspartate receptor-induced activation of p21(ras) - Yun, Hye-Young (The National Academy of Sciences, 1998)
N-methyl-d-aspartate (NMDA) glutamate receptor-mediated increases in intracellular calcium are thought to play a critical role in synaptic plasticity. The mechanisms by which changes in cytoplasmic calcium transmit the glutamate signal to the nucleus, which is ultimately important for long-lasting neuronal responses, are poorly understood. We show that NMDA receptor stimulation leads to activation of p21(ras) (Ras) through generation of nitric oxide (NO) via neuronal NO synthase. The competitive NO synthase inhibitor, l-nitroarginine methyl ester, prevents Ras activation elicited by NMDA and this effect is competitively reversed by the NO synthase substrate, l-arginine. NMDA receptor stimulation fails to activate Ras in neuronal cultures from mice lacking neuronal NO synthase. NMDA-induced Ras activation occurs through a cGMP-independent pathway as 1H-[1,2,4]oxadiazolo[4,3-alpha]quinoxalin-1-one (ODQ), a potent and selective inhibitor of guanylyl cyclase, has no effect on NMDA receptor-induced activation of Ras, and the cell-permeable cGMP analog, 8Br-cGMP, does not activate Ras. Furthermore, NO directly activates immunoprecipitated Ras from neurons. NMDA also elicits tyrosine phosphorylation of extracellular signal-regulated kinases, a downstream effector pathway of Ras, through a NO/non-cGMP dependent mechanism, thus supporting the physiologic relevance of endogenous NO regulation of Ras. These results suggest that Ras is a physiologic target of endogenously produced NO and indicates a signaling pathway for NMDA receptor activation that may be important for long-lasting neuronal responses.